Neoliberalismo e sofrimento psíquico: aspectos da questão da moradia na cidade de São Paulo e no Brasil - Lima, Tatiana Rute Pontes (2022)
This research sheds light on the direct connection between neoliberalism and psych suffering in the housing issue. To build this connection, this research begins by addressing the material consequences of neoliberalism and the ways in which it is inserted in local economies in a process that is observed globally that alters the configuration of the State and represents a constant violation of the rights of the population. In a context of helplessness, is possible to observe the psychic suffering. To understand psychic suffering, a rescue is made of the concepts of neoliberal subjectivity and the articulation of individuals' desires. The material consequences of neoliberalism serve as the social context for the psychic suffering. For this analysis, the concept of neoliberal subjectivity is rescued, in which the subject finds himself in a constant logic of competitiveness in his psychic life and his desires are guided by the neoliberal logic. Therefore, the issue of housing is brought up as a location where these processes are expressed and demonstrates a neoliberal predatory logic. Finally, the rescue of the collectivity is observed through the Landless Worker’s Movement as a way out of a place of passivity to a place of resistance